“FALSE SHEIKH” CRITIQUE IN DAGESTAN IN THE END OF THE 19TH – EARLY 20TH CENTURIES (ON THE EXAMPLE OF THE WORK OF HASAN-HILMI AL-KAKHI “DURRA AL-BAYDA’ FI RADDI-L-BADA’ WA-L-AHWA”) - Sehmagomedov, Magomed Gadzievic (History, Archeology and Ethnography of the Caucasus, 2021)
Based on a brief source analysis of an Arabic-language work of a prominent Dagestan Sufi sheikh Hasan-Hilmi al-Kakhi “Durra al-bayda’ fi raddi-l-bada’ wa-l-ahwa” (A shining pearl for the refutation of innovations and whims), the article reveals the essence of an inter-Sufi dispute between the followers of different Sufi brotherhoods, which took place in Dagestan at the end of the 19th – early 20th centuries. This dispute was expressed in mutual criticism and accusations of some Sufi figures of being “false sheikhs”. The polemics were mainly initiated by the representatives of the Mahmudiyya branch of the Naqshbandi brotherhood; their opponents were the representatives of the Khalidiyya branch, which at that time amounted to the largest number of followers. One of the most active participants in the inter-Sufi polemics was the Naqshbandi sheikh Hasan-Hilmi al-Kakhi. In his work “Durra al-bayda’ fi raddi-l-bada’ wa-l-ahwa” al-Kakhi strongly criticizes some Dagestani Sufis, who, in his opinion, illegally engage in mentoring activity without the appropriate investiture, and thereby discredit the Sufi teaching. In the same work, al-Kakhi first attempted to classify the “Dagestani false sheikhs.” He devoted several more of his later works to this issue, in which he generalized and supplemented his ideas, while his positions on some issues and the rhetoric itself changed greatly. Al-Kakhi’s criticism provoked a backlash from his opponents. This problem was also reflected in the Arabic-language polemical works of other Dagestan Sufi contemporaries. The study of this issue is an important part in revealing the history of the spread and development of Sufism in Dagestan.
Keywords: Sufism; Naqshbandiyya; al-Kakhi; criticism; false sheikhs; polemics; Dagestan